2012
DOI: 10.1007/s00221-012-3026-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pedaling exercise on the intracortical inhibition of cortical leg area

Abstract: Pedaling is widely used for rehabilitation of locomotion because it induces similar muscle activity to that observed during locomotion. However, no study has examined the effects of pedaling exercise on intracortical inhibition. The aim of the present study was to investigate the effect of pedaling exercise on short-interval intracortical inhibition (SICI) in the cortical area controlling the tibialis anterior (TA) and soleus (SOL) muscles. Ten healthy adults participated in this study and were instructed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
1
37
1
Order By: Relevance
“…As indicated, previous research has demonstrated a decrease in SICI in exercising muscles [7]. The current results extend this finding to non-exercised muscles and indicate that such changes are not a direct consequence of preceding muscle activity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As indicated, previous research has demonstrated a decrease in SICI in exercising muscles [7]. The current results extend this finding to non-exercised muscles and indicate that such changes are not a direct consequence of preceding muscle activity.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, pedaling exercise has been shown to decrease intracortical inhibition in the leg region of M1 [7], which suggest that such an intervention may be effective in increasing excitability. However, in clinical settings, spasticity and muscle weakness are seen frequently in the upper limbs, particularly following a stroke.…”
Section: Introductionmentioning
confidence: 99%
“…However, some reports using transcranial magnetic stimulation, a more sensitive marker of motor corticospinal output, have suggested modulations within M1 following acute aerobic exercise (Yamaguchi et al. ; Singh et al. ; Smith et al.…”
Section: Discussionmentioning
confidence: 99%
“…98 The effects of these paradigms on motor recovery are unknown; they have been suggested because of their documented effect on corticomotor excitability. Compared to stimulation-based priming, research on movement-based strategies to prime the motor system is minimal.…”
Section: Introductionmentioning
confidence: 99%